Induced polarization method in hydrocarbon prospecting - WOJDYŁA, Marek; STEFANIUK, Michał; SADA, Marek; SITO, Łukasz (Geology, Geophysics and Environment, 2011)
The paper presents the method of induced polarization (IP) and focuses on its application to direct prospecting for hydrocarbon deposits. Induced polarization parameters that are obtained from measurements in time domain and frequency domain are presented. Classification of minerals and rocks based on induced polarization parameter was analyzed. Five examples of application of induced polarization method to discovering and recognizing hydrocarbon deposits by foreign companies were given. Methodology of field works made in Carpathians and Carpathian Foredeep with the use of equatorial and dipole-dipole arrays was described. Maps of phase parameter evaluated from results of equatorial array measurements for Grabownica and Rudka deposits as well as the plot of phase parameter along profile cutting the area of Rylowa deposit were analyzed. Cross-sections of three induced polarization parameters were made and analyzed with CSAMT resistivity sections in the area of Rudka deposit.